Multifocal Gorham-Stout disease associated with Chiari I malformation and recurrent aseptic meningitis: Case report and review of literature. (February 2020) - Stephens, Sean; Squires, Lisa; Campbell, Robert; Davies, Janene; Chaseling, Raymond
Highlights: Gorham-Stout disease (GSD) is characterised by lymphatic proliferation and osteolysis. First case of multifocal disease involving skull base, with Chiari 1, and meningitis. Craniocervical restenosis occurred following decompression likely from occiput settling. Recurrent aseptic CSF pleocytosis without CSF fistula confounded, delayed diagnosis. Review showed poor outcomes of Chiari decompression amid GSD. Abstract: Gorham-Stout disease is a rare condition of uncertain aetiology characterised by lymphatic proliferation within osseous structures and subsequent massive osteolysis. This report describes the index case of a patient with multifocal Gorham-Stout disease involving the skull base with Chiari I malformation and recurrent aseptic meningitis without fistula. A five-year-old male presented following decompression of a Chiari I malformation with headaches, vomiting, and stiff neck and cerebrospinal fluid pleocytosis without growth of a pathogenic organism. Ongoing symptoms prompted a further three presentations over several months revealing persistent aseptic cerebrospinal fluid monocytic pleocytosis. Further investigation revealed multifocal osseous cystic disease and subsequent bone biopsy suggested Gorham-Stout disease. Suboccipital decompression was not repeated despite craniocervical junction re-stenosis. A literature review demonstrated the extreme rarity of Gorham-Stout disease associated with Chiari I malformation and meningitis. Potential mechanisms of these entities occurring in concert are discussed. Consideration of Gorham-Stout disease as a secondary cause for Chiari I malformation is important amid local bone changes or cerebrospinal fluid leakage prior to pursuing suboccipital decompression considering the poor outcomes reported.